PENDAMPINGAN PENGEMBANGAN SISTEM INFORMASI JUAL BELI MAKELAR MOTOR DI KABUPATEN PEKALONGAN BERBASIS WEB - Mahardika, Fajar; Al’ Amin, M. (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2024)
Community service is an activity that aims to help a particular community in several activities. This activity is one part of the Tri Dharma of Higher Education, an educational activity in the community in the form of introducing website-based motorbike sales technology. This technology was introduced in order to increase sales of motorbikes, especially to 2-wheeled motorbike brokers. The program partner is the two-wheeled motorbike broker community in Kedungwuni sub-district, Pekalongan district. With many problems occurring, one of which is lack of sales and lack of knowledge of buyers as well as crime when purchasing vehicles. In this service, we developed a motorbike sales application that utilizes advances in information technology to overcome these obstacles. This application is designed with a user-friendly interface, so it can be used easily by the realtor community. In the framework of this service, we also carry out outreach and training to the broker community regarding the use of this application. The aim is for the realtor community to optimize their motorbike sales potential through this application, as well as obtain other benefits, such as wider access to the market and efficiency of time and energy. Through this service, it is hoped that it can increase efficiency and effectiveness in the motorbike sales process, as well as provide benefits to the broker community in increasing access to the market. The results of program implementation show that the broker community received the training quite well with a score of 66.5%.